2022
DOI: 10.31620/jccc.06.22/14
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Payment Adoption Among Youth: Generation Z and Developing Country Perspective

Abstract: This paper aims to understand the factors that influence mobile payment adoption among youth concerning Generation Z customers, who are the most significant drivers of mobile payments, specifically in developing countries. Data was collected through a questionnaire accomplished by 365 undergraduate students between 18 to 22 years of age. The partial least square structural equation modelling (PLS-SEM) analysis instituted the behavioural intention to adopt mobile payments was substantially and positively affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Recent post-COVID-19 research aligns with these results, highlighting the significance of technology's ease of use and adaptability in shaping business conduct and decision-making processes [33], [55]. Research conducted by sources [32], [56], and [57] reveals a strong correlation between business expectations and the inclination towards technology use, particularly in a fast-changing digital environment. The observation aligns with the fact that many MSME participants belong to the younger demographics.…”
Section: Discussionmentioning
confidence: 66%
“…Recent post-COVID-19 research aligns with these results, highlighting the significance of technology's ease of use and adaptability in shaping business conduct and decision-making processes [33], [55]. Research conducted by sources [32], [56], and [57] reveals a strong correlation between business expectations and the inclination towards technology use, particularly in a fast-changing digital environment. The observation aligns with the fact that many MSME participants belong to the younger demographics.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, across all adoption situations, trust in the security and privacy of the payment system emerges as a critical predictor (Sleiman et al, 2021). Younger and better educated consumers frequently show increased adoption, which is influenced by demographic characteristics as well (Purohit et al, 2022;Wei et al, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Nevertheless, there is a scarcity of scholarly investigations that specifically examine the determinants impacting the acceptance and utilization of mobile payment systems, especially within the settings of developing economies (Raj et al, 2023). In addition, there is limited academic research on the acceptability of mobile wallets among young cohorts such as Generation Z (born 1997-2012), despite their inclination towards early adoption of new technologies (Purohit et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven to have a variety of effects on the individuals' intentions to use new technology services. Researches by Rahim, Bakri, Fianto, Zainal, & Shami (2022), Abrahão et al (2016), Abu-Taieh et al (2022), Alkhwaldi, Alharasis, Shehadeh, Abu-AlSondos, Oudat, & Atta (2022), Almaiah, Al-Rahmi, Alturise, Alrawad, Alkhalaf, Lutfi, & Awad (2022), Chan, Troshani, Hill, & Hoffmann (2022), Farah, Hasni, & Abbas (2018), Purohit, Kaur, & Chaturvedi (2022), and Tan & Lau (2016) found that the behavioral intentions of the users of the latest technology were significantly influenced by the performance expectancy. However, Boonsiritomachai & Pitchayadejanant (2019) and Sebastián, Antonovica, & Guede (2023) demonstrated the opposite, where the users' behavioral intention to adopt new financial technology was not significantly influenced by the performance expectancy.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%